PENDIDIKAN KARAKTER MELALUI NILAI KEARIFAN LOKAL DI ERA GLOBAL - Nur Rahmat (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
character education become an important element in developing the realm of effective for school age children basic and invested in children age basic in order to establish a private learners who have the value of sublime and create learners smart cognitively. Purpose of this research is to find out comprehensively the importance of education in developing the wisdom of local packed modern way to maintain the values of the local to embed National character in the younger generation. Research method in use is qualitative. Data obtained through research by way of observations, interviews and documentation. Research results in Elementary country 3 rejosari district belitang mulya district Oku East show that character education adopt values in the local knowledge as the value of religious, mutual assistance, Arts and literature, and skill of local. In this study the benefits of character education through the value of wisdom that bear generations competent and dignified; reflect cultural values; participate in the form the nation's character, contribute to the creation of the identity of the nation and contribute in preserving the nation's cultural; give creative ideas for teachers to develop the material character education for learners through the value of wisdom, motivate teachers and parents in order to direct the learners to be a private intelligent and cultured and preserve the cultural property that is in the local area.  Keywords- character education, the value of local knowledge, and globalization